2016
DOI: 10.2147/ijn.s99911
|View full text |Cite
|
Sign up to set email alerts
|

Improvement and enhancement of antibladder carcinoma cell effects of heteronemin by the nanosized hyaluronan aggregation

Abstract: The effects against tumors exerted by marine active compounds have been highlighted and investigated. Polymeric nanoparticles made from biodegradable and biocompatible molecules such as hyaluronan (HA) and chitosan (CHI) are able to aggregate the compounds to enhance their activities against tumor cells and reduce the toxicity on normal cells. Here, we extensively examined the antitumor activities and the mechanisms of HA/CHI nanoparticles-aggregated heteronemin (HET) extracted from the sponge Hipp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 32 publications
3
15
0
Order By: Relevance
“…Heteronemin exhibited potent cytotoxicity against both androgen-dependent and -independent type of human prostate cancer cells including PC3, LNcap and Du145 cancer cell lines [ 19 ]. Previous studies reported multiple biological activities of heteronemin, including antitubercular, cytotoxic, anti-intravasative activities [ 15 , 19 , 59 , 60 ]. Heteronemin induced renal cancer cells apoptosis and autophagy mediated by the suppression of Akt and MAPK pathway [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heteronemin exhibited potent cytotoxicity against both androgen-dependent and -independent type of human prostate cancer cells including PC3, LNcap and Du145 cancer cell lines [ 19 ]. Previous studies reported multiple biological activities of heteronemin, including antitubercular, cytotoxic, anti-intravasative activities [ 15 , 19 , 59 , 60 ]. Heteronemin induced renal cancer cells apoptosis and autophagy mediated by the suppression of Akt and MAPK pathway [ 14 ].…”
Section: Discussionmentioning
confidence: 99%
“…Heteronemin is a spongean sesterterpenoid, which acts against different kinds of cancers [2,3] with low or non-cytotoxicity to non-malignant cells [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…In our previous study, HAn at concentrations between 10 and 40 μg/mL did not inhibit cell viability in L929 normal fibroblasts [ 12 ]. Encapsulation of natural compounds by using HAn has also been found to decrease the cell viability inhibitory effects of pure compounds in L9292 normal cells [ 13 ]; this further highlights the advantages of HAn aggregation and encapsulation. DMSO has been demonstrated to inhibit early growth response gene expression, arrest mouse embryo fibroblasts in the cell cycle and damage mitochondrial integrity and membrane potential in murine astrocytes [ 18 , 19 ].…”
Section: Resultsmentioning
confidence: 99%
“…In our previous studies, we successfully fabricated HA nanoparticles (HAn) using an electrostatic field system (EFS) in an aqueous-phase environment to encapsulate drugs and demonstrated that HAn-derived drug aggregates have antitumor effects. Evidence has further shown that aggregation/encapsulation of HA nanoparticles enhances antitumor effects of potential compounds and drugs [ 12 , 13 , 14 , 15 ]. HA is an anionic, nonsulfated, water-soluble polysaccharide and it is biologically essential to cellular functions.…”
Section: Introductionmentioning
confidence: 99%